Therapeutic effects of short-term trauma stabilization techniques combined with escitalopram in treating adolescent major depressive disorder: a pilot randomised controlled trial - Jiating Xu; Jiajia Wu; Xiaojing Wang; Qianqian Chen; Ruizhi Xu; Yaoyan Xu; Xiuchao Geng; Yiping Tang (BMC Psychiatry)
Abstract Objective To explore the efficacy of short-term trauma stabilization techniques combined with escitalopram in the treatment of adolescent major depressive disorder (MDD). Methods A total of 80 patients with MDD who were hospitalized in the Psychosomatic Department of our hospital were selected and randomly divided into two groups: the escitalopram combined with short-term trauma stabilization technique group (study group) and the escitalopram combined with mental health education group (control group). Upon hospitalization, patients completed the adolescent self-rating life events check list (ASLEC), impact of event scale-revised (IES-R), 17-item Hamilton depression scale (HAMD-17) and Hamilton anxiety scale (HAMA). After 2 and 4 weeks of treatment, the IES-R, HAMD-17-17 and HAMA scores were reevaluated. Results There were no significant differences in the ASLEC, IES-R, HAMD-17 or HAMA scores between the two groups at admission. Compared with that of the control group, the IES-R score of the study group was significantly improved at the 2nd week of treatment (P < 0.01). By the 4th week of treatment, the IES-R scores in the study group had further improved compared to the control group (P < 0.01). Additionally, the HAMD-17 and HAMA scores in the study group were significantly improved compared to the control group (P < 0.01). Conclusion Escitalopram combined with short-term trauma stabilization is more effective in the treatment of MDD than escitalopram with mental health education, warranting further exploration.